Venous Malformations and Blood Coagulation in Children - Johanna Aronniemi; Satu Långström; Katariina A. Mattila; Anne Mäkipernaa; Päivi Salminen; Anne Pitkäranta; Johanna Pekkola; Riitta Lassila (MDPI AG, 2021)
Introduction: Venous malformations (VMs) are congenital low-flow lesions with a wide spectrum of clinical manifestations. An increasing number of studies link VMs to coagulation abnormalities, especially to elevated D-dimer and decreased fibrinogen. This condition, termed localized intravascular coagulopathy (LIC), may pose a risk for hemostatic complications. However, detailed data on the laboratory variables for coagulation and fibrinolytic activity in VM patients are limited. We addressed this question by systematically analyzing the coagulation parameters in pediatric VM patients. Methods: We included 62 patients (median age 11.9 years) with detailed laboratory tests for coagulation and fibrinolytic activity at a clinically steady phase. We assessed clinical and imaging features of VMs and their correlations with coagulation and fibrinolysis variables using patient records and MRI. Results: D-dimer was elevated in 39% and FXIII decreased in 20% of the patients, as a sign of LIC. Elevated D-dimer and decreased FXIII were associated with large size, deep location, and diffuse and multifocal VMs. FVIII was elevated in 17% of the patients and was associated with small VM size, superficial and confined location, discrete morphology, and less pain. Surprisingly, antithrombin was elevated in 55% of the patients but without associations with clinical or other laboratory variables. Conclusions: LIC was common in pediatric patients with VMs. Our results provide a basis for when evaluating the risks of hemostatic complications in children with VMs. Further research is warranted to explore the mechanisms behind coagulation disturbances and their relation to clinical complications.